Unexpected Effect of Calcium Channel Blockers on the Optic Nerve Compartment Syndrome - Konieczka, K.; Todorova, M. G.; Bojinova, R. I.; Binggeli, T.; Chackathayil, T. N.; Flammer, J. (Klinische Monatsblätter für Augenheilkunde, 2016)
Background: The optic nerve compartment syndrome is a pathological condition in which cerebrospinal fluid of the subarachnoid space surrounding the optic nerve is partly or totally segregated from the cerebrospinal fluid of the intracranial subarachnoid space, leading – inter alia – to an increase in the diameter of the optic nerve sheath. The pathogenesis of this condition remains unclear. We have observed clinically that optic nerve compartment syndrome often occurs in normal tension glaucoma patients with Flammer syndrome. To treat Flammer syndrome, some glaucoma patients received a low dose of a calcium channel blocker and we analysed whether this treatment also had an effect on the optic nerve compartment syndrome.Patients and Methods: We retrospectively analysed the data of 10 eyes of seven patients suffering from a combination of primary open angle glaucoma, optic nerve compartment syndrome, and Flammer syndrome. We included subjects who had eye socket echography before and after a few months of therapy with a calcium channel blocker.Therapy and Results: All patients received a low dose of a calcium channel blocker (nifedipine or amlodipine) to treat Flammer syndrome. As expected, the symptoms of Flammer syndrome were mitigated. To our surprise, the optic nerve compartment syndrome also improved in eight of the 10 eyes (80 %), but remained unchanged in the remainder.Conclusions: To some extent, the optic nerve compartment syndrome is related to the combination of primary open angle glaucoma and Flammer syndrome. On the basis of our results, we hypothesise that treatment of Flammer syndrome may also improve the optic nerve compartment syndrome.
Keywords: optic nerve compartment syndrome (ONCS); Flammer syndrome (FS); primary vascular dysregulation (PVD); primary open angle glaucoma (POAG); calcium channel blockers; endothelin-1